2016
DOI: 10.1055/s-0042-114704
|View full text |Cite
|
Sign up to set email alerts
|

Tumorprothesen in der endoprothetischen Revisionschirurgie der unteren Extremität – Ergebnisse von 25 Patienten nach Versorgung mit einem modularen Tumor- und Revisionssystem (MUTARS®)

Abstract: With extended life expectancy, the number of primary joint arthroplasties has also increased. Revision surgery is also more often necessary, due to aseptic or septic loosening of the prosthesis or periprosthetic fracture. Large bone defects often occur in these patients and several non-modular, conventional implants are available to handle this difficult situation. Custom made implants offer an individually designed and defect-adapted shape with perfect covering of the lesion, but may delay the operation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
8
0
3
Order By: Relevance
“…2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series. 4,5,20,22,23 The overall 12 % infection rate of the presented study is almost identical to the previously published series of mixed primary resections with revision arthroplasty where Glehr et al 27 reported an infection rate of 12.5 % among 32 patients who had been treated with MUTARS® silver-coated endoprostheses and Wafa et al 18 reported an overall postoperative infection rate of 11.8 % in the silver-coated group of 85 Agluna-Stanmore Implants. Likewise, Schmolders et al 4 had to perform revision operations due to infection in 10 % of their implanted silver-coated MUTARS® endoprostheses after a median follow-up of 24 months for primary or metastatic oncological patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series. 4,5,20,22,23 The overall 12 % infection rate of the presented study is almost identical to the previously published series of mixed primary resections with revision arthroplasty where Glehr et al 27 reported an infection rate of 12.5 % among 32 patients who had been treated with MUTARS® silver-coated endoprostheses and Wafa et al 18 reported an overall postoperative infection rate of 11.8 % in the silver-coated group of 85 Agluna-Stanmore Implants. Likewise, Schmolders et al 4 had to perform revision operations due to infection in 10 % of their implanted silver-coated MUTARS® endoprostheses after a median follow-up of 24 months for primary or metastatic oncological patients.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the results in revision arthroplasty patients are difficult to analyse within or between different centres due to different diagnostic methods of infection (e.g., sonication), perioperative antibiotic regiments, number of previous surgical procedures and pre-existing infections. All these limitations were also present in all other recent studies of this topic [1][2][3][4][5][6][19][20][21][22][23][24] where the infection-rate variability of silver-coated implants was larger between different patient populations (primary resection, metastases, revision, previous infection) and anatomical localizations than between different implant types (silver-coated vs. non-coated). 2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Until now, modularity in THA is mainly applied in revision and tumor arthroplasty [ 15 18 ]. In primary THA modular implants are barely used because of the high risk of breakage [ 11 , 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modularen Revisionsschaftsystemen nicht gut versorgbar ist. Durch die Arbeitsgruppe von Schmolders et al [5] wurde daher die Anwendung eines modularen tumorendoprothetischen Systems (MUTARS) in der femoralen Revisionsendoprothetik untersucht. Es zeigte sich aufgrund der einfachen Handhabung intraoperativ mit modularer Adaptation an die vorliegende Defektsituation (vom proximalen Femurersatz bis zum totalen Femur) eine für diese komplexen Fälle akzeptable Komplikationsrate von insgesamt 24 %.…”
unclassified